Examining the “Forest Law” in Los Lagos, Argentina, Through the Lens of Mapuche Organisations - Valverde, Sebastián (2021)
In 2007 Argentina passed the ‘Federal Law 26331 on Minimum Standards for the Environmental Protection of Native Forests’, often referred to as the Forest Law, aimed at curbing and regulating the expansion of the agricultural frontier causing deforestation and the loss of native forests, and amid increasing social conflict. The law mandated provinces to develop and-use planning and zoning of their native forests through a participatory process, and to classify different uses of forestlands. In the province of Neuquén, the application of this regulation –along with its equivalent provincial norm, Law 2780-triggered much debate among environmental and social organizations, unions, small-scale rural producers, and Mapuche indigenous organizations, leading to an increase in conflict and disagreements between the different sectors involved. The application of the Forest Law in the region of Los Lagos and Lacar departments, which are forest areas with high landscape attractiveness and increasing tourism and real estate activity, generated considerable controversy, mobilizations, and debate in the local arena. Research for this paper involved methodological triangulation through ethnography and legal hermeneutics.